Análise de pluma hiperpicnal poli-dispersa por simulação numérica direta - Schuch, Felipe Nornberg (2016)
The studies on transport mechanics and sediment deposition in bed slope channels has rapidly increased over the last decade, this is associated with the fact that they play a fundamental role on the formation of hydrocarbon reservoirs. This work aims to investigate, through direct numerical simulation, the plunge phenomena dynamics when a heavier density fluid, full of particles, flows into a lower density environment. Simulations were carried out with Incompact3d, a code based on a Boussinesq system for incompressible fluids was utilized. The channel’s entrance sediment concentration and flow rate influence on the plunge point and deposition profiles were investigated. Results are compared with theoretical models and physical experiments.